PELVIC FLOOR MUSCLE EXERCISE IMPROVING SEXUAL SELF-EFFICACY - Nolla Lisa Lolowang; Yati Afiyanti; Titin Ungsianik (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
Sexuality is one of the most important components of a person's quality of life. Postpartum is the period when women experienced problems in their sexual lives. This study aimed to prove the effects of pelvic floor muscle (PFM) exercise on sexual self-efficacy among primiparous women. This research was a quasi-experiment study with one group time series design, with the number of respondents 32 people. The results showed that the intervention of pelvic floor muscle exercise which performed for six weeks proved to increase the sexual self-efficacy of primiparous mother significantly (p = 0,001; CI 95% 10,53 – 14,18). PFM exercise is the best way to increase pelvic floor muscle strength that positively affects the enhancement of sexual self-efficacy of primiparous women. It is recommended that PFM exercise become a nursing intervention that should be explained and taught by nurses as a form of postpartum care education.Keywords: PFM exercise, sexual self-efficacy.